EFFECTS OF DATE SEED EXTRACTION (ROASTED AND NON-ROASTED) AS A POTENTIAL TO INHIBIT ADIPOGENESIS OF BONE MARROW MSCS - Amer Mahmood; Mona Elsafadi; Muthurangan Manikandan; Abdul-Aziz Siyal; Randa Alfotawi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Mesenchymal stem cell (MSCs) are multipotent stem cells and can differentiate into different cell types and can proliferate for long time. These two characteristics make MSCs an excellent source for regenerative medicine to treat various diseases and injuries. Objectives: The objectives of the present study are to find the effects of date seed extraction (roasted and non-roasted) as a potential to inhibit adipogenesis of bone marrow MSCs. Materials and Methods: Bone marrow mesenchymal stem cell lines (human MSCS) is a gift from our collaborator from Denmark Professor Mousta Kassems lab in Odense. Cells were cultured in Dulbecco’s Modified Eagle Medium (DMEM) that includes D-glucose 4500 mg/L, 110 mg/L sodium pyruvate, 4 mM L-glutamine, 10% fetal bovine serum (FBS), non-essential amino acids (Gibco-Invitrogen, USA), and 1x penicillin–streptomycin (Pen–strep). Results: The viability of the cells grown has been evaluated using the AlmarBlue according to the standard protocol described. A total of six plates were divided between roasted and non-roasted date seed extracts. The cell viability of these plates was measured on day 1, day 2 and day 3 using AlmarBlue. Moreover, we measured the cell viability of the remaining two plates of the 24 well-plate on day 9 for cells incubated with different concentrations of roasted and non-roasted date seed extract with or without adipocyte induction medium CNT. The intensity of fluorescence is proportional to the number of living cells in treated samples and CNT. AlmarBlue assay showed that roasted date extract manifested high cell viability on day 1 and day 2 compared to day 3 which showed a reduction in cell viability. The cell viability of extract from roasted date seed showed high metabolic activity showed at 50, 500 and 1000 concentrations on day two. Conclusion:The present study showed that roasted and non-roasted date seed extract were significantly reducing adipocyte differentiation compared to the control group. We observed that non-roasted date seed extract significantly reduces adipocyte with 100 g/ml concentration and above. Practical Implications: These results may have clinical implications for diabetic patients since date seed extract has anti-adipogenic, anti-oxidants, anti-bacterial and anti-viral effects. Further studies are needed to determine the correct dose of date seed extract.